The Evolution of Student Monitoring Systems in School Buses: A Detailed Review - Anita H. Shinde; Vishal Dhage; Apeksha Nagane; Rasheshwari Menkudale (International Journal of Electrical Machine Analysis and Design, 2024)
In modern educational institutions, ensuring the safety and well-being of students during transportation is paramount. To address this, we propose a comprehensive Student Monitoring System for buses, designed to enhance safety, efficiency, and communication between stakeholders. The system utilizes advanced technologies such as GPS tracking, RFID tags, and real-time data processing to monitor students' location, track bus routes, and provide instant notifications to parents and school administrators. By integrating these technologies, the system offers features including real-time location tracking, attendance recording, emergency alerts, and optimized route planning. Moreover, the system facilitates seamless communication between parents, drivers, and school authorities through mobile applications and web interfaces. This paper outlines the design, implementation, and evaluation of the Student Monitoring System, highlighting its effectiveness in ensuring the safety and security of students during their commute. Additionally, ethical considerations, privacy safeguards, and future enhancements are discussed to address concerns and further improve the system's functionality and usability.
Keywords: GPS tracking; RFID Tags; Real Time Data Processing; biometric scanners; mobile application